PENGHIDUPAN KEMBALI PASAL TERHADAP PENGHINAAN PRESIDEN DAN WAKIL PRESIDEN DALAM RANCANGAN KITAB UNDANG-UNDANG HUKUM PIDANA - Rahmasari, Nuzul Shinta Nur; Soeskandi, Hari (Mimbar Keadilan, 2022)
Law Number 1 of 1946 concerning of Criminal Law is an affirmation made by the government from the enactment of Colonial Law known as Wetboek van Strafrecht (WvS) or widely known as Kitab Undang-Undang Hukum Pidana (KUHP). KUHP itself should be revised with the current condition of the Indonesia. However, the revision of Criminal Law within the draft of KUHP itself consist articles which cause conflict, one of which is the article about insult directed President and/or Vice President of the Indonesia. Wheres, this article is already removed by the Constitutional Court in 2006 under the statementNumber 013/022/PUU-IV/2006. The Governmment and House of Representatives seem to have disobeyed the statement of the Constitutional Court that makes the writer of this journal decides to take the revival of the article of insult to President and/Vice President as the background of the problem of a research. Further analysis will be carried out by the writer regarding the insult of President’s dignity and honor then analyze the policy of reactivating the said article about insult of the leader of the country in RKUHP by central government and House of Representatives. The said article is considered unconstitutional by Constitutional Court (MK) and has been objected to be a part of the RKUHP or articles with the same and similar contents. The process of the analysis will still use the reference from Constitutional Court’s decision and experts’ opinion. This reserach uses juridical normative approach which aim to discover rules and also norms to answer the legal issue being faced so that the solutions of the issue in this research can be made. In this case, the reactivation of the article of insult directed to the leader of the country in RKUHP is not the proper policy to be made because it has a tendency to be used as a tool to silent the people’s voice to criticize the performance of the President and/Vice President.